A novel iPSC-based model of ICF syndrome subtype 2 recapitulates the molecular phenotype of ZBTB24 deficiency - Lullo, Vincenzo; Cecere, Francesco; Batti, Saveria; Allegretti, Sara; Morone, Barbara; Fioriniello, Salvatore; Pisapia, Laura; Genesio, Rita; Della Ragione, Floriana; Giardino, Giuliana; Pignata, Claudio; Riccio, Andrea; et al. (Frontiers in Immunology, 2024)
Immunodeficiency, Centromeric instability and Facial anomalies (ICF) syndrome is a rare genetic disorder characterized by variable immunodeficiency. More than half of the affected individuals show mild to severe intellectual disability at early onset. This disorder is genetically heterogeneous and ZBTB24 is the causative gene of the subtype 2, accounting for about 30% of the ICF cases. ZBTB24 is a multifaceted transcription factor belonging to the Zinc-finger and BTB domain-containing protein family, which are key regulators of developmental processes. Aberrant DNA methylation is the main molecular hallmark of ICF syndrome. The functional link between ZBTB24 deficiency and DNA methylation errors is still elusive. Here, we generated a novel ICF2 disease model by deriving induced pluripotent stem cells (iPSCs) from peripheral CD34+-blood cells of a patient homozygous for the p.Cys408Gly mutation, the most frequent missense mutation in ICF2 patients and which is associated with a broad clinical spectrum. The mutation affects a conserved cysteine of the ZBTB24 zinc-finger domain, perturbing its function as transcriptional activator. ICF2-iPSCs recapitulate the methylation defects associated with ZBTB24 deficiency, including centromeric hypomethylation. We validated that the mutated ZBTB24 protein loses its ability to directly activate expression of CDCA7 and other target genes in the patient-derived iPSCs. Upon hematopoietic differentiation, ICF2-iPSCs showed decreased vitality and a lower percentage of CD34+/CD43+/CD45+ progenitors. Overall, the ICF2-iPSC model is highly relevant to explore the role of ZBTB24 in DNA methylation homeostasis and provides a tool to investigate the early molecular events linking ZBTB24 deficiency to the ICF2 clinical phenotype.